URGENSI TEORI MAQASHID AL-SYARI’AH DALAM PENETAPAN HUKUM ISLAM DENGAN PENDEKATAN MASHLAHAH MURSALAH - Yakin, Ainul (JURNAL AT-TURAS, 2015)
Along with the change and development of society that is rapidly increasing, the legal issues are more increasingly complex. While some legal problems that developed in the community are not all explicitly mentioned either in the Quran, hadith and ijma‘. While the Islam as a religion must always be responsive and present to provide a solution to the legal developing problems. Mashlahah mursalah as one method of extracting law-although still disputed or suited to address legal issues that developed nowdays. However, in order to use mashlaah mursalah to explore and establish a law is not stuck to the things that are subjective and interests of lust, the use of such methods necessary prudence and understanding maqasidsyariah intact and use of mashlahahmursalah in strict compliance with the criteria set by scholar’s ushul order to reach and find the laws that really fit with the message maker law (syariah).